Reframing and Recontextualizing Maria Montessori’s 1915 California Visit - Parham, Joel (Journal of Montessori Research, 2023)
Maria Montessori’s visit to California in 1915—her second visit to the United States—coincided with multiple events in the region: San Francisco’s Panama–Pacific International Exposition (PPIE), San Diego’s Panama–California Exposition (PCE), and the National Education Association of the United States (NEA) annual meeting in Oakland. Her visit also came at a time when the American Montessori movement was splintering, and the academic elite increasingly criticized her educational model. These circumstances made Montessori’s visit to California a potentially valuable opportunity to rekindle interest in Montessori education across the United States. Discussions of Montessori’s visit in 1915 have been framed around her training course and demonstration school at the PPIE. Based on information from primary sources (e.g., newspapers and archival materials), some of which have been overlooked, this article asserts that her visit to California had broader implications. While her eight months in California did have a positive impact on the growth of the Montessori movement, Montessori’s engagement with mainstream education had limited impact and it gave way to waning interest in Montessori education in the United States.